Encourage Teacher Innovative Behavior : The Interaction Role of Cognitive Flexibility and Teacher Self-Efficacy - Dumbi, Khairunnisa Syafira; Indrasari, Stephanie Yuanita (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the interaction role of cognitive flexibility and teacher self-efficacy in teacher innovative behavior in the context of curriculum change in Indonesian schools. This study used a quantitative survey method. Three instruments were used, namely the Teacher Innovative Behavior Scale, the Cognitive Flexibility Inventory, and the Teachers’ Sense of Efficacy Scale. Data were collected from 322 teachers from three educational levels in Jabodetabek. Descriptive analyses, correlation analyses, and moderation analyses were conducted. The findings revealed that cognitive flexibility, as a whole construct, and each dimension (the control and alternative dimension), positively predicts teacher innovative behavior. Specifically, only the alternative dimension that significantly interacts with teacher self-efficacy positively predicts teacher innovative behavior. In other words, teacher self-efficacy is significant as a moderator. The findings highlight the importance of addressing cognitive flexibility and teacher self-efficacy, which were not extensively researched before, in enhancing teachers’ innovative behavior. Innovative behavior is crucial for teachers, especially in the current era of change.